117k views
4 votes
P 3 • p 2 • p

Multiply or divide as indicated.
heeelllpppp

1 Answer

0 votes

For this case we have the following expression:


p ^ 3 * p ^ 2 * p =

By definition of multiplication of powers of the same base, we have to put the same base and add the exponents, that is:


a ^ n * a ^ m = a ^ {n + m}

So:


p ^ 3 * p ^ 2 * p = p^( 3 + 2 + 1) = p^6

Answer:


p^6

User Nick Sarafa
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.